Banking Stock Market Reaction to the Announcement Bank Indonesia Interest Rate Event: Announcement of BI Benchmark Interest Rate Reduction, By the Board of Governors Meeting, August 19, 2025 - Islamiah; Iwan Kusmayadi (Al-Kharaj: Journal of Islamic Economic and Business, 2026)
This study examines the reaction of banking sector stocks on the Indonesia Stock Exchange to Bank Indonesia's announcement of a 25 basis point BI-Rate cut to 5.00 percent on August 19, 2025. The objective is to assess the market response through abnormal returns around the event. Using a comparative quantitative approach with an event study method, the population is all listed banking issuers, a purposive sample of 41 companies with complete daily closing price data. Secondary data from the IDX and the Jakarta Composite Index (JCI) are analyzed through a market model on the estimation window t-40 to t-11, AR and AAR calculations on the event window t-10 to t+10, Wilcoxon Signed-Rank test due to non-normal data (α = 0.05). The results show no significant difference in AAR before the event (mean = 0.002638, SD = 0.018113) and after (mean = 0.002395, SD = 0.008696), with p = 0.164. In conclusion, the policy did not cause a market surprise because it had been anticipated.